Forest cover changes and public policy: A literature review for post-conflict Colombia. (March 2022) - Vanegas-Cubillos, M.; Sylvester, J.; Villarino, E.; Pérez-Marulanda, L.; Ganzenmüller, R.; Löhr, K.; Bonatti, M.; Castro-Nunez, A.
Abstract: Tackling deforestation remains a significant challenge in tropical countries and even more so in those affected by armed conflicts. This is partly because of the limited local understanding of the causes of forest cover changes (FCC) and how these causes relate to development. In this study, we use Colombia as a model to contribute to the understanding of the links between the causes of FCC in conflict-affected countries and policies aimed at achieving sustainable development by targeting the agriculture, forestry and other land use (AFOLU) sectors. Specifically, we reviewed studies reporting on causes of FCC from 1995 to 2019 to build a state-of-the-art review. We then identified relevant public policies targeting AFOLU sectors and used them as a proxy for development. Finally, we discussed the links between these public policies and FCC. From the reviewed literature, it is clear that research on FCC in Colombia has focused on understanding the causes of forest cover losses while disregarding forest cover gains. Although cattle ranching and agriculture dominate the literature as proximate causes of deforestation and policy and institutional factors as underlying causes of deforestation, the relative importance of proximate and underlying causes of FCC in Colombia has changed over time. The main categories of policies that have been linked to FCC deal with conflict and post-conflict issues, coca eradication and, more recently, the implementation of the peace agreement. Another set of policies frequently mentioned are those related to productive activities. In Colombia, these policies' effects on forests will depend on how the state will regulate extractive activities in a post-conflict scenario. Therefore, it is imperative to review and update policies to tackle FCC, mainly deforestation, to successfully achieve sustainability targets in Colombia. Highlights: Colombia is emerging conflict and has set ambitious targets for halting deforestation. This review analyze links between deforestation and land use policies in Colombia. Cattle ranching and agriculture are the main proximate causes of deforestation. Policies to eradicate conflict and institutional factors the main underlying ones. It is imperative to update sustainable development policies in light of evidence.